Different Conceptualizations of River Basins to Inform Management of Environmental Flows - Gawne, Ben; Capon, Samantha J.; Hale, Jenni; Brooks, Shane S.; Campbell, Cherie; Stewardson, Michael J.; Grace, Mike R.; Stoffels, Rick J.; Guarino, Fiorenzo; Everingham, Penny (Frontiers in Environmental Science, 2018)
Environmental flows are a critical tool for addressing ecological degradation of river systems brought about due to increasing demand for limited water resources. The importance of basin scale management of environmental flows has long been recognised as necessary if managers are to achieve social, economic and environmental objectives. The challenges in managing environmental flows are now emerging and include the time taken for changes to become manifest, uncertainty around large-scale responses to environmental flows and that most interventions take place at smaller scales. The purpose of this paper is to describe how conceptual models can be used to inform the development, and subsequent evaluation of ecological objectives for environmental flows at the basin scale. Objective setting is the key initial step in environmental flow planning and subsequently provides a foundation for effective adaptive management. We use the implementation of the Basin Plan in Australia’s Murray-Darling Basin (MDB) as an example of the role of conceptual models in the development of environmental flow objectives and subsequent development of intervention monitoring and evaluation, key steps in the adaptive management of environmental flows. The implementation of the Basin Plan was based on the best science available at the time, however, this was focused on ecosystem responses to environmental flows. The monitoring has started to reveal that limitations in our conceptualisation of the basin may reduce the likelihood of achieving of basin scale objectives. One of the strengths of the Basin Plan approach was that it included multiple conceptual models informing environmental flow management. The experience in the MDB suggests that the development of multiple conceptual models at the basin scale will help increase the likelihood that basin-scale objectives will be achieved.